Carotid Endarterectomy After Intracranial Endovascular Thrombectomy for Acute Ischaemic Stroke in Patients with Carotid Artery Stenosis. (March 2022) - Jonsson, Magnus; Aro, Ellinoora; Björses, Katarina; Holmin, Staffan; Ijäs, Petra; Martinez-Majander, Nicolas; Vikatmaa, Pirkka; Wahlgren, Carl-Magnus; Venermo, Maarit; Björck, Martin
Abstract : Objective: Recent randomised controlled trials demonstrated the benefit of intracranial endovascular thrombectomy (EVT) in acute ischaemic stroke. There is no consensus, however, on how to treat concomitant extracranial carotid artery stenosis after EVT. The aim of this study was to evaluate the outcome in patients treated with carotid endarterectomy (CEA) after EVT, comparing complication rates among patients undergoing CEA for stroke without previous EVT. Methods: This was a registry study of all patients ( n = 3 780) treated with CEA after stroke in Sweden and the capital Helsinki region, Finland, from January 2011 to September 2020. Sixty three patients (1.7%; 0.5% 2011, 4.3% 2019) underwent EVT prior to CEA. The primary outcome was 30 day stroke and death rate. Results: The EVT+CEA group had major stroke as the qualifying neurological event (QNE) in 79%, but just 5.9% had this in the CEA only group ( p < .001). Intravenous thrombolysis was administered before EVT in 54% of patients in the EVT+CEA group, but in just 12% in those receiving CEA only ( p < .001). The combined stroke and death rate at 30 days for EVT+CEA was 0.0% (95% confidence interval [CI] 0.0 – 5.7). One patient had a post-operative TIA, none had post-operative intracerebral or surgical site haemorrhage. CEA was performed within a median of seven days (interquartile range 4, 15) after QNE, and 75% had CEA ≤14 days from QNE. The main reason to postpone CEA was an infarct larger than one third of the middle cerebral artery territory. The stroke and death rate in patients treated with CEA only was 3.7% (95% CI 3.2 – 4.4), CEA was performed a median of eight days after QNE, and in 79.7% in ≤14 days. The three year survival after EVT+CEA was 93% (95% CI 85 – 100), compared with 87% (95% CI 86 – 88) after CEA only. Cox regression analysis adjusting for age showed no increased all cause mortality after EVT+CEA (HR 1.3, 95% CI 0.6 – 2.7, p = .52). Conclusion: These results indicate that CEA is safe to perform after previous successful EVT for acute ischaemic stroke. Results were comparable with those undergoing CEA only, despite the EVT+CEA patients having more severe stroke symptoms prior to surgery, and timing was similar.